2015
DOI: 10.1159/000381642
|View full text |Cite
|
Sign up to set email alerts
|

A 4-Year, Open-Label, Multicenter, Randomized Trial of Genotropin® Growth Hormone in Patients with Idiopathic Short Stature: Analysis of 4-Year Data Comparing Efficacy, Efficiency, and Safety between an Individualized, Target-Driven Regimen and Standard Dosing

Abstract: Background/Aims: Growth hormone (GH) treatment regimens for children with non-GH-deficient, idiopathic short stature (ISS) have not been optimized. To compare the efficacy, efficiency, and safety of an individualized, target-driven GH regimen with standard weight-based dosing after 4 years of treatment. Methods: This is a 4-year, open-label, multicenter, randomized trial comparing individualized, formula-based dosing of Genotropin® versus a widely used ISS dose of Genotropin®. Subjects were prepubertal, had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
(46 reference statements)
1
11
0
Order By: Relevance
“…The adverse events reported in the study were consistent with the safety profile of GH in patients with ISS, and IGF-I was not increased excessively ( 1 , 3 , 8 , 31 , 32 ). Because GnRH agonist therapy is associated with decreased BMD, concerns have been raised concerning potential fractures due to the reduced bone accretion ( 12 ).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The adverse events reported in the study were consistent with the safety profile of GH in patients with ISS, and IGF-I was not increased excessively ( 1 , 3 , 8 , 31 , 32 ). Because GnRH agonist therapy is associated with decreased BMD, concerns have been raised concerning potential fractures due to the reduced bone accretion ( 12 ).…”
Section: Discussionsupporting
confidence: 76%
“…Various studies have shown that growth hormone (GH) treatment of children with ISS can increase their growth velocity and, to a lesser extent, adult height ( 1 , 2 , 3 , 4 , 5 , 6 ). The effect on height is variable and depends, among other factors, on dose and age at GH initiation ( 7 , 8 , 9 , 10 ). GH treatment for ISS was approved in the United States in 2003 and has not been approved in the EU ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, the use of Genotropin®, a biosimilar product, has been studied in an open-label, multicenter, randomized trial. After 4 years of treatment, 316 children with idiopathic short stature in all treatment regimens achieved similar average height gains; however, the individualized dosing regimen utilizing less GH reached an equivalent height gain [ 37 ].…”
Section: Reviewmentioning
confidence: 99%
“…Growth responses vary without a clear relationship between hGH dose and height SDS change in children with ISS [32] who often have presentations and laboratory findings similar to partial IGHD. In such children, results vary as to whether individualized GH responsiveness formula-based hGH dosing does [33] or does not [34] achieve targeted height gain during the first years of treatment with lower variability. Thus, in practice, it is still reasonable to initiate hGH treatment at a dose typically used to treat GHD and then titrate upward as needed to sustain a desired growth rate [35].…”
Section: Cost-conscious Steps To Preserve Necessary Hgh-for-height Trmentioning
confidence: 99%
“…Thus, in practice, it is still reasonable to initiate hGH treatment at a dose typically used to treat GHD and then titrate upward as needed to sustain a desired growth rate [35]. Importantly, following a period of catch-up growth, hGH doses – and costs – can usually be reduced without decline in height SDS [34]. While short-term data suggest that targeting hGH dosing to IGF-1 levels may improve growth response [36], it is not known whether adult height is improved, or long-term risks increased [37] by such titration, and more to the point, whether such hGH dose escalation is a necessary or cost-conscious approach to achieving a satisfactory therapeutic objective.…”
Section: Cost-conscious Steps To Preserve Necessary Hgh-for-height Trmentioning
confidence: 99%